Absolute blood levels and kinetics of neurofilament light (NFL) chains for neurological prognosis in comatose patients after cardiac arrest - Timothée Ayasse; Maxime Touron; Marie-Céline Blanc; Estelle Pruvost-Robieux; Jean-Baptiste Lascarrou; Clara Vigneron; Jean-Paul Mira; Frédéric Pène; Alain Cariou; Sarah Benghanem (Annals of Intensive Care)
Abstract Introduction Despite current guidelines, the prognosis of comatose patients after cardiac arrest (CA) remains indeterminate in approximately 50% of patients. Neurofilament light (NFL) chain, a biomarker of neuronal injury, appears to be a promising tool with better prognostic value compared to neuron-specific enolase (NSE). However, further studies are required. The objective was to evaluate the prognostic value of absolute blood levels and kinetics of NFL measured at 24, 48 and 72 h after CA to predict outcome. Methods A prospective study conducted at a tertiary CA center conducted between April 2023 and November 2024, including 67 comatose patients after CA with at least one blood NFL measurement. The primary outcome was neurological outcome according to the “best” modified Rankin scale (mRS) within 3 months, with a mRS 0–3 defining a good outcome. Results Participants were 64 years old (IQR [53–75]), and 67% were male. 60% of them had out-of-hospital CA and 42% had an initial shockable rhythm. NFL levels were significantly higher in patients with unfavorable outcome compared to those with favorable outcome at each time point (24 h: 256.0 [96.2–441.9] versus 37.9 [17.4–104.5] pg/mL, p < 0.001; 48 h: 1297.7 [137.6–3605.0] versus 36.4 [19.3–174.0] pg/mL, p < 0.001; 72 h: 1591.9 [350.6–4913.5] versus 49.3 [23.2–146.4] pg/mL, p < 0.001). NFL levels at 24 and 48 h showed moderate prognostic accuracy (AUC 0.80 and 0.88, respectively), while NFL at 72 h demonstrated high accuracy (AUC 0.90). For predicting poor outcome, NFL level at 24 h > 250 pg/mL had a specificity of 0.90 [0.75–0.90] and a sensitivity of 0.51 [0.35–0.67]. At 48 h, NFL > 383 pg/mL had a specificity of 0.94 [0.81–1.00] and a sensitivity of 0.66 [0.50–0.81]. At 72 h, NFL > 510 pg/mL presented a specificity of 1.00 [1.00–1.00] and a sensitivity of 0.74 [0.52–0.91]. To predict a good outcome, NFL levels < 82 pg/mL at 24 h, < 307 pg/mL at 48 h and < 459 pg/mL at 72 h after CA were the best compromise between specificity and sensitivity. NFL kinetic was not associated with neurological outcomes (AUC 0.50), whereas NSE kinetic measured between 24 and 72 h showed high prognostic accuracy (AUC 0.92). Conclusion In comatose patients after CA, NFL levels at 24, 48 and 72 h could predict both unfavorable and favorable outcomes. Conversely, only the kinetic of NSE levels between 24 and 72 h after CA was associated with neurological outcome.